Review on The Paper Making Process From Bamboo As A Paper Product - SHAMSURI, MUHAMMAD AKIF (Progress in Engineering Application and Technology, 2021)
Bamboo is a grass that can grow to 25 m in six months. Every culm emerges from the ground at its final diameter (i.e. its girth does not extend over its lifetime), tapering as it rises in height, and increasing vertically by "telescopically" cell division between nodes (i.e., the distance between nodes increases as it grows). When fully cultivated, it takes normally three to five years to grow to full strength, during which they are silified and lignified. This study aims to review the papermaking process from bamboo as a paper product. The density (for bamboos), fiber dimensions, morphological indices, and chemical composition of the raw materials studied were determined. The Kraft, pulping processes were applied and some of the pulps produced were bleached according to the D_0EpD_1 bleaching sequences (where D represents chlorine dioxide and Ep represents peroxide reinforced alkaline extraction) bleaching methods. The fiber dimensions were microscopically evaluated. The average fiber length of bamboo is around 2.29 mm for length, 16.4 µm for total width, 6.4 µm for wall thickness, and 3.5 µm for lumen diameter. According to flexibility coefficients, bamboo has higher bonding strength (tensile, burst, double folds). The thicker wall of Gigantochloa scortechinii (9 µm) compared to other bamboo indicated very different morphological indices and behavior. The chemical composition of the raw materials was typical for non-woody plants. They have high ash content and low lignin contents. The very good cellulose content of bamboo can make very good pulp yield. The higher cellulose content (52.7%) of Melocanna Baccifera predicted better yields. The overall chemical composition indicates the suitability of alkaline methods for pulping with reasonable alkali charges and predicted good to excellent yields. This was demonstrated by cooking with different alkali charges.